Siebeck curves and two refinements of the - Casas-Alvero, Eduardo (Mathematica Scandinavica, 2012)
We prove two results which improve the well known Gauss-Lucas theorem by locating the roots of the derivative of a complex polynomial $f$ in sets smaller than the convex hull of the roots of $f$.